AB0370 Association of Clinical Efficacy with Serum Level of Adalimumab (ADA) and Anti- Adalimumab Antibody Levels in Patients with Early Rheumatoid Arthritis (RA). (10th June 2014) - Avdeeva, A.S.; Aleksandrova, E.N.; Novikov, A.A.; Karateev, D.E.; Luchihina, E.L.; Cherkasova, M.V.; Nasonov, E.L.
Abstract : Background: ADA is effective and safe drug for the treatment of RA. Application of ADA can be accompanied by formation anti-adalimumab antibody (anti-ADA Ab) influencing on efficiency of therapy and the development of adverse events Objectives: To evaluated the correlation of serum levels of ADA and anti-ADA Ab in relation to clinical response in patients (pts) with early RA Methods: Serum levels of ADA (μg/ml) and anti-ADA Ab (positive/negative result) was determined by ELISA in 25 pts with early RA (15 women, mean age – 54, 0; 47, 0-58, 0 years, mean disease duration - 8, 0; 5, 0-25, 0 months, mean DAS 28 – 5, 8; 4, 9-7, 5, SDAI 34, 3; 22, 8-54, 2, CDAI 32, 0; 21, 7-48, 4) baseline and then after 12 and 24 weeks of treatment. All patients received disease-modifying antirheumatic drugs (DMARDs) (100%>methotrexate) and ADA 40mg every 2 weeks. For all patients the ADA was the first biologic Results: On the 12-th week of therapy values [Me; interquartile range] DAS 28 were 3, 5 (3, 2-4, 4); SDAI-13, 0 (7, 0-16, 6); CDAI - 10, 8 (7, 0-16, 0), 6 pts achieved a good EULAR response, 14- moderate response. On the 24-th week of treatment the value DAS 28 were 3, 5 (3, 1-4, 4), SDAI-11, 7 (7, 4-17, 5) and CDAI - 10, 5 (6, 2-16, 3), a good response was noted at 7 patients, moderate response - at 9 pts. The pts was distributed in two groups from serum levels of ADA: <3, 0 (the first group n=7) and ≥3, 0 (second group n=13). There were no differences between the groups on disease activity, level of acute-phase reactants by the 12th week of therapy (p>0, 05). Higher disease activity and also the level of acute-phase reactants were marked out among pts of the first group (DAS 28 – 4, 5; 3, 3-4, 9, ESR – 44; 18-57 mm/h, CRP -10, 1; 4, 9-34, 5 mg/ml) compared with pts of the second group (3, 5; 2, 9-3, 9, 15, 0; 6, 0-17, 0 mm/h, 1, 9; 0, 75-6, 7 mg/ml, respectively, p<0, 05) by the 24th week of therapy. Also on the 24th week negative correlation was found with level of ADA and DAS 28 (r= -0, 46; p=0, 04), CRP (r= -0, 54; p=0, 02) and ESR (r= -0, 5; p=0, 02). Anti-ADA Ab was found in 3 (12, 5%) pts at week 12 and in 2 (10%) pts at week 24. By 24th week of treatment at 100% of pts with presence of anti-ADA Ab was absence of clinical effect (ΔDAS28 = -1, 36; -3, 1-0, 4). In the group of pts without anti-ADA Ab we found fewer of "no respondents" (11%) and identified positive dynamics DAS 28 (ΔDAS28=2, 5; 1, 66-2, 9) (p<0, 05) Conclusions: Low drug level (<3, 0 μg/ml) in serum is associated with a high clinical and laboratory disease activity at pts with early RA receiving the ADA therapy. By 12-24 weeks of ADA therapy anti-ADA Ab is found in 10-12, 5% of pts, it's formation is accompanied of decrease in efficacy of therapy Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2266